Chemical and in silico exploration of novel 5-hydroxytryptamine 2A receptor (5-HT2AR) ligands - Damerum, Luke (2024)
The 5-HT2AR is a target in neuropsychiatric conditions such as psychosis, which is commonly managed with atypical antipsychotics. These have associated side effects due to off-target interactions. Consequently, there is a demand to develop therapeutics that exhibit no affinity for these off-target sites. Moreover, in recent 5-HT2AR X-ray crystal structures, a unique hydrophobic pocket or passage between transmembrane helices 4 and 5 sets it apart from other 5-HT2 receptor subtypes. This structural feature is implicated in the selectivity demonstrated by therapeutic pimavanserin towards the 5-HT2AR, owing to its binding conformation. Thus, presenting it as a target to interrogate for enhancing 5-HT2AR binding.